Development of Learning Management Model to Enhance Communication Ability in Listening and Speaking English for Pratom Suksa 5 Students. Watbhurapaphiram Municipal School, Department of Education, Roi Et Municipality, Roi Et Province - Chomphubut, Ubon (Academic Journal of Mahamakut Buddhist University Roi Et Campus, 2019)
The objectives of the research were to 1)study conditions. compliance and the need to enhance learning. Ability to communicate in listening and speaking English, 2) develop a learning management model to enhance communication ability in listening and speaking English, 3) study the effects of learning management model to enhance communication ability in listening and speaking English. Samples students Pratom Suksa 5. Watbhurapaphiram Municipal School, Department of Education, Roi Et Municipality, Roi Et Province, 23 were used in the research. Lesson plans based learning management model to enhance communication ability in listening and speaking English for Pratom Suksa 5 Students. Teachers guide for learning management model to enhance communication ability in listening and speaking English. Tests listening and speaking. The statistics used in this study consisted of an average percentage, standard deviation. Test and t – test. The research found that: 1. basic data analysis study, which contains basic information about the person document. Such data can be used in defining. The capabilities, behavior, and indicator development learning management model to enhance communication ability in listening and speaking English for Students 5. Watbhurapaphiram Suksa Pratom Municipal School, Department of Education, Roi Et Municipality, Roi Et Province has the learning activity consists of 6 elements, namely, 1. Principle 2. Objective 3. Syntax step, learning management system, covering the 5. The steps. 4. Principle of Reaction 5. Support System 6. Evaluation 2. The results of the development of learning management model to enhance communication ability in listening and speaking English which is a proof of suitability and consistency that have high value. 3. Results based learning management model to enhance communication ability in listening and speaking English for Pratom Suksa 5 Students. Students have the skills of listening and speaking English. Increased after an activity-based learning as a role model, a statistically significant level .05 4. The results of the evaluation of learning management model to enhance communication ability in listening and speaking English for Pratom Suksa 5 Students as a whole. the high level.